Radiopharmaceutical good practices: Regulation between hospital and industry - Faivre-Chauvet, Alain; Bourdeau, Cécile; Bourgeois, Mickaël (Frontiers in Nuclear Medicine, 2022)
Radiopharmaceutical practices are divided into large-scale industrial manufacturing and small-scale “in-house” hospital radiopharmacy unit. The recent evolution of nuclear medicine involves deep consequences in this ever-present regulatory state, and hospital radiopharmacy units cannot be considered as contract manufacturing organizations (CMO). This review provides an updated status report of the official (and non-official) guidelines supporting the regulations required to meet hospital and industry common radiopharmaceutical manufacturing standards to facilitate the current and future innovative radiopharmaceutical development.